Fertility Effects on Female Labor Supply: IV Evidence from IVF Treatments - Petter Lundborg; Erik Plug; Astrid Würtz Rasmussen (Institute for the Study of Labor (IZA), 2014)
This paper introduces a new IV strategy based on IVF induced fertility variation in childless families to estimate the causal effect of having children on female labor supply using IVF treated women in Denmark. Because observed chances of IVF success do not depend on labor market histories, IVF treatment success provides a plausible instrument for childbearing. Our IV estimates indicate that fertility effects are: (a) negative, large and long lasting; (b) much stronger at the extensive margin than at the intensive margin; and (c) similar for mothers, not treated with IVF, which suggests that IVF findings have a wider generalizability.
Keywords: J13; J22; 330; children; extensive and intensive fertility margins; female labor supply